How patients perceive the role of hospital chaplains: a preliminary exploration. Issue 3 (September 1995) - Ellis, J M; McManus, C; Newton, B A
Abstract : OBJECTIVE–An exploratory study of the attitudes of hospital patients to the service provided by hospital chaplains. DESIGN–Questionnaire study of hospital inpatients in December 1992. SETTING–One large teaching hospital in London. PATIENTS–180 hospital inpatients in 14 different general wards, 168 (93%) of whom agreed to take part. MAIN MEASURES–Attitudes to chaplains and their role contained in 12 questions developed during a pilot study on hospital inpatients (16) and staff (14) and their relation to patients' age, sex, length of hospital stay, and religious beliefs, according to Kendall rank order correlations. RESULTS–Of 168(93%) respondents, 72(43%) were women; mean age of patients was 63.1 (SD 16.8) years. Forty five (27%) were inpatients of three days or less and 22(13%) for one month or more. 136(81%) were Christian; 17(10%) atheist, agnostic, or had no religion; and 15(9%) were of other religions. In general, patients showed positive attitudes towards the role of hospital chaplains and to the services they provided. The correlation analysis showed that there was a significant tendency for older patients, those who had been inpatients for longer, and those with religious beliefs to be more sympathetic to the role of hospital chaplains. CONCLUSIONS–Hospital chaplains provide a service which is appreciated by patients. This study provides a simple instrument for assessing patients' attitudes to chaplains.